2018
DOI: 10.1080/14764172.2017.1418510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy between long-pulsed Nd:YAG laser and pulsed dye laser to treat rosacea-associated nasal telangiectasia

Abstract: Both LPNY and PDL are effective in treating rosacea-associated nasal telangiectasia. If LPNY is used properly to avoid side effects with careful consideration, it can also be used as a good modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…Kwon et al compared two different lasers, pulsed dye laser (PDL) and Nd:YAG(LPNY), and concluded that PDL is more safe and effective in the treatment of erythema and mild telangiectasia, while LPNY is better on thicker dilated vessels 5 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kwon et al compared two different lasers, pulsed dye laser (PDL) and Nd:YAG(LPNY), and concluded that PDL is more safe and effective in the treatment of erythema and mild telangiectasia, while LPNY is better on thicker dilated vessels 5 …”
Section: Discussionmentioning
confidence: 99%
“…The laser devices that have been used the most for nasal telangiectasia are CO2 laser, potassium titanyl phosphate (KTP) laser, long‐pulsed neodymium:yttrium‐aluminum‐garnet Nd:YAG(LPNY) laser, erbium:yttrium‐aluminum‐garnet laser, and intense pulsed light (IPL) 2,5 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations